Procalcitonin-guided antibiotic therapy for pediatrics with infective disease: A updated meta-analyses and trial sequential analysis - Li, Peng; Liu, JiaLe; Liu, Junjun (Frontiers in Cellular and Infection Microbiology, 2022)
Objective We aim to evaluate the effect of procalcitonin (PCT) guided therapy on antibiotic exposure in pediatric patients with acute respiratory infection. Methods We undertook an updated systematic review and meta-analysis of randomized controlled trials (RCTs) identified in systematic searches of MEDLINE, EMBASE, the Cochrane Database, Google Scholar and SinoMed (through July 2021). Primary outcome was length of antibiotic therapy. Required information size (RIS) was calculated with trial sequential analysis (TSA). Results Four RCTs with 1313 pediatrics with acute respiratory infection were included. Overall, after a mean 22 days follow-up, PCT-guided antibiotic therapy was associated with significantly shorter length of antibiotic therapy compared with the control group (WMD, -2.22 days; 95% CI, -3.41 to -1.03; P<0.001) and decreased rate of antibiotic adverse events (RR, 0.25; 95% CI, 0.11–0.58; P<0.001). However, length of hospital stay (WMD, -0.39 days; 95% CI, -0.84 to 0.07; P=0.094), rates of antibiotics prescription (RR, 1.10; 95% CI, 0.97–1.25; P=0.122), hospital readmission (RR, 1.03; 95% CI, 0.92–1.16; P=0.613) and mortality (RR, 0.73; 95% CI, 0.17–3.19; P=0.674) were comparable between the PCT-guided antibiotic and control groups. TSA showed that the RIS was 2340, and indicated statistically significant shorter length of antibiotic therapy between PCT-guided antibiotic and control groups (P<0.05). Conclusions PCT-guided management seems to be able to decrease antibiotics exposure for pediatrics with acute respiratory infection. However, much larger prospective clinical studies are warranted to confirm these findings.